External and Internal Conflicts of the Main Character in the Movie Clouds - Leoni, Ni Kadek (Udayana Journal of Social Sciences and Humanities; Vol 7 No 2 (2023): Vol 7 No 2 (2023): UJoSSH, September 2023DO - 10.24843/UJoSSH.2023.v07.i02.p05, 2024)
Ni Kadek Leoni 1 , I Made Suastra 2 , Ni Luh Putu Krisnawati 3   Abstract : This study is entitled External and Internal Conflict of the Main Character in the Movie Clouds. The aim is to analyze the kinds of conflict and to find out the strategies of main character to manage the conflict in the movie Clouds. The documentation method also the technique used to collect the data in this study note-taking technique and qualitative descriptive method was used as a method and technique of analyzing data based on the theory by Kenney and the theory by Deetz and Stevenson . The results show two types of conflict found in Clouds movie: External and Internal Conflict. The most appear conflict in conversation is external conflict than internal conflict. The most applied conflict management shows in the movie are avoidance, compromise, and pacification because that is relevant resolution conflict to the topic in conversation.